The Drift Diffusion Model can account for the accuracy and reaction time of value-based choices under high and low time pressure - Milica Milosavljevic; Jonathan Malmaud; Alexander Huth; Christof Koch; Antonio Rangel (Judgment and Decision Making, 2010)
An important open problem is how values are compared to make simple choices. A natural hypothesis is that the brain carries out the computations associated with the value comparisons in a manner consistent with the Drift Diffusion Model (DDM), since this model has been able to account for a large amount of data in other domains. We investigated the ability of four different versions of the DDM to explain the data in a real binary food choice task under conditions of high and low time pressure. We found that a seven-parameter version of the DDM can account for the choice and reaction time data with high-accuracy, in both the high and low time pressure conditions. The changes associated with the introduction of time pressure could be traced to changes in two key model parameters: the barrier height and the noise in the slope of the drift process.